Drama and the curriculum. Issue 1 (2nd January 2016) - Goodlass, Ray
Abstract: In this article from nearly 40 years ago, Ray Goodlass discusses key issues relating to drama's place in the curriculum. He draws on key theorists and practitioners from the time, including Slade, Way, Heathcote and Courtney, to illustrate major considerations in the arts and drama curriculum design process. Goodlass considers a range of curriculum models, reminding us that it is to our advantage to consider the full range of possibilities.